The Salazar documents : Insquisitor Alonso de Salazar Frías and others on the Basque witch persecution - Henningsen, Gustav (Cultures, beliefs, and traditions ;, 2004)
A bilingual edition of eye-witness reports on an early 17th-century witch panic or dream epidemic in the Basque country, written by a Jesuit, a Bishop, and a Spanish Inquisitor who analysed the phenomenon empirically from psychological and anthropological standpoints.